Pengaruh Pijat Oksitoksin, Untuk Melancarkan Asi Pada Ibu Post Partum P0A1 Dengan Partus Spontan Di Ruang Mawar RSUD Waled - Sindia Devi, Nadia; Sari Purbaningsih, Endah; Mamay Maftuha, Indah; Khasanah, Uswatun; Rimawati Nurokhman, Neneng (MEJORA Medical Journal Awatara, 2024)
Newborn babies need to receive optimal care from birth, one of which is ideal food. Breast milk (ASI) is the most recommended food for babies for at least the first 6 months of life. However, in reality, exclusive breastfeeding is not as easy as imagined. Various obstacles can arise in efforts to provide exclusive breastfeeding during the first six months of a baby's life. This research aims to provide the application of oxytocin massage in post-partum maternal care to overcome the problem of ineffective breastfeeding. The research design used in this research is a case study of a post partum mother P0A1 with spontaneous labor in the Mawar room at Waled Hospital, Cirebon Regency. This research was carried out at Waled Hospital, Cirebon Regency, precisely in the Mawar Room on January 5 2024. Breast milk production can be accelerated with non-pharmacological measures, namely through oxytocin massage which can be done by massaging the area around the back (pars thoracic vertebrae) to stimulate the release of breast milk. The mother will feel satisfied, happy, confident, because she can give breast milk to her baby. the problem of ineffective breastfeeding related to inadequate breast milk supply was resolved and a little milk came out and the patient said that after the oxytocin massage the patient felt comfortable and relaxed